2019
DOI: 10.15642/ijet2.2019.8.2.15-25
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Kit Built Concept Mapping to Help Non-English Department Students Improve their Reading Skills

Abstract: Reading skill is important especially for non-English departments students like those of Information Technology Department at State Polytechnic of Malang. However, based on the observation and the results of the tests, the students showed low performance and motivation in reading English written texts even though the texts were on IT related subjects. Therefore, the students were introduced to Kit-Built Concept Mapping to help them overcome the problems. This study is Classroom Action Research (CAR) to analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…For example, Lechuga et al (2015) found that the concept mapping technique was not as effective as retrieval practice in a learning test. Asri and Andoko (2019) found that concept mapping was not entirely successful for improving students' reading skills. Additionally, Wilson and Kim (2016) found that concept mapping did not significantly increase reading comprehension achievement.…”
Section: Effects Of Concept Maps In Esl/efl Reading Comprehensionmentioning
confidence: 95%
See 2 more Smart Citations
“…For example, Lechuga et al (2015) found that the concept mapping technique was not as effective as retrieval practice in a learning test. Asri and Andoko (2019) found that concept mapping was not entirely successful for improving students' reading skills. Additionally, Wilson and Kim (2016) found that concept mapping did not significantly increase reading comprehension achievement.…”
Section: Effects Of Concept Maps In Esl/efl Reading Comprehensionmentioning
confidence: 95%
“…It is crucial, however, to acknowledge the presence of limitations accompanying these approaches. According to Asri and Andoko's (2019) study, the implementation of KB mapping was not fully successful in improving students' reading skills, despite questionnaire and interview results indicating increased student interest and motivation to read. It is worth noting that KB mapping requires students to have a good command of software and computer skills, and schools need to provide sufficient equipment, which may not be practical for all classrooms in various regions where teaching for ESL/EFL reading takes place.…”
Section: Research Trends and Effectiveness Of Concept Mappingmentioning
confidence: 97%
See 1 more Smart Citation
“…"Bil-İste-Öğren", "BİÖ", "KWL", "Know-Want to Know-Learned", K-W-L" anahtar sözcükleriyle DergiPark, ULAKBİM, YÖK Tez Tarama sayfası, Google Akademik ve ERIC ve EBSCOhost veri tabanlarında yapılan araştırmalar sonucunda BİÖ stratejisi kullanılarak yapılmış çeşitli çalışmalara rastlanmıştır. Bunlardan bazıları (Alabsi, 2018;AlAdwani vd., 2022;Al-Shaye, 2002;Ardiyan, 2022;Asri, 2014) BİÖ stratejisinin okuduğunu anlamaya etkisiyle ilgili deneysel ve kuramsal çalışmalardır. Alan yazın taraması sonucunda BİÖ stratejisinin yazma becerisinde kullanımına dair çalışmalar (Cantrell vd., 2000;Fengjuan, 2010;Herlina, vd., 2013;Khayriddinkizi, 2021;Lou vd., 2016;Shintia, 2021;Susanti, 2014;Zubaidah vd.,2021) ve konuşma becerisinde kullanımına dair çalışmalar (Lubis, 2019;Mantra, 2016;Sugiyarti, 2008; ) yapıldığı da görülmüştür.…”
Section: Introductionunclassified
“…Studies in this area mostly focused on variety of method as to enhance students' score gains. The methods range from blending learning (Komariah et al, 2017), cooperative learning the enactment of Students Team Achievement Division (STAD) (Rionaldi & Saputra, 2019), low-cost videos (Asri et al, 2022), and the implementation of TOEFL practicum class (Djamereng et al, 2021).…”
Section: Introductionmentioning
confidence: 99%